Association of HPA Axis Hormones with Copeptin After Psychological Stress Differ by Sex - Spanakis, Elias K. (Psychoneuroendocrinology, 2015)
INTRODUCTION: Copeptin levels are elevated in severe medical conditions, an effect that is attributed to elevated arginine vasopressin (AVP) levels in response to physiological stress, resulting in activation of hypothalamus-pituitary-adrenal (HPA) axis. In the current study, we wanted to determine if copeptin is responsive to psychological stress, correlates with cortisol and adrenocorticotropin hormone (ACTH), and if associations differed by sex. MATERIALS AND METHODS: In a cross-sectional study that included 100 healthy men (41%) and women (59%) (aged 18–30 years; mean 24.6±3 years), who underwent the Trier Social Stress Test (TSST), we examined the association between percent change (peak-baseline/baseline) in copeptin levels and percent change in log ACTH and cortisol. Three baselines samples were drawn followed by blood sampling at 20, 35, 50, 65 and 85 min after TSST. RESULTS: There was a significant positive association between the percent change in copeptin and the percent change in log-transformed salivary cortisol (β-coefficient=0.95; p=0.02). The association between percent change in copeptin and log-transformed serum cortisol was not statistically significant in the overall population. There was a trend for a non-significant association between percent change in copeptin and percent change in log-transformed ACTH (β-coefficient=1.14; p=0.06). In males, there was a significant positive association between the percent change in copeptin levels and log-transformed salivary (β-coefficient=1.33, p=0.016) and serum cortisol (β-coefficient=0.69, p=0.01), whereas in women there was no statistically significant association. CONCLUSIONS: We found a significant positive association between percent change in copeptin and percent change in salivary and serum cortisol among males only.